Enzyme mediated synthesis of water-dispersible, naturally protein capped, monodispersed gold nanoparticles; their characterization and mechanistic aspects - Khan, Shadab Ali; Ahmad, Absar (RSC Advances, 2014)
Inorganic nanomaterials are conventionally synthesized under harsh environments like extremes of temperature, pressure and pH. These methods are eco-unfriendly, expensive, toxic, cumbersome, yield bigger particles which agglomerate due to not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions viz. room temperature, atmospheric pressure, physiological pH and is reliable, eco-friendly and cheap. We have already reported the extracellular biosynthesis of monodispersed gold nanoparticles from the whole cells of novel extremophilic actinomycete Thermomonospora sp. In order to know the exact mechanism of synthesis, we decided to investigating it further. Here we describe the simple protocol for purification of the temperature and SDS resistant sulfite reductase enzyme and organic capping molecule, which are required for the synthesis and stabilization of gold nanoparticles respectively. This purified enzyme was then employed for the synthesis of gold nanoparticles along with the capping molecule, which render gold nanoparticles monodispersed in solution.